2020
DOI: 10.1088/1361-6579/ab8e5f
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis and dual x-ray absorptiometry agreement for skeletal muscle mass index evaluation in sarcopenia diagnosis

Abstract: Background: All definitions for diagnosing sarcopenia include the estimation of muscle mass. This can be made using bioelectrical impedance analysis (BIA) or dual x-ray absorptiometry (DXA). BIA is a portable and inexpensive method suitable for clinical settings, while DXA is cumbersome, more expensive and less available. Objectives: To evaluate the interchangeability of both techniques for skeletal muscle mass index (SMI) estimation, and assess whether the two methods are comparable for the diagnosis of sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…However, until now, the measured values by MF-BIA were heterogeneous in accuracy compared with DEXA or MRI and showed differences in the diagnosis rate of sarcopenia in various studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Nine studies evaluated the correlation between MF-BIA and DEXA for assessing muscle mass [ 30 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, the measured values by MF-BIA were heterogeneous in accuracy compared with DEXA or MRI and showed differences in the diagnosis rate of sarcopenia in various studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Nine studies evaluated the correlation between MF-BIA and DEXA for assessing muscle mass [ 30 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to precisely answer this as many factors influence low LTM onset, progression and diagnosis 35 . Moreover, it was demonstrated that the prevalence varies with age 12 , methods of evaluation (DXA or bioelectrical impedance) 36 , and the cut-offs used 14 . A meta-analysis of 19 studies demonstrated an overall low LTM prevalence of 17% of older Brazilians aged ≥ 60 years 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Because it is defined by a decrease in skeletal muscle mass, the skeletal muscle index (SMI) is useful for the evaluation of sarcopenia ( 13 ). The methods of measuring the SMI include measuring the cross-sectional area of the muscle by examining images, such as computed tomography (CT) and magnetic resonance imaging (MRI); bioelectrical impedance analysis (BIA); and dual-energy X-ray absorptiometry (DEXA) ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%